PENGARUH PENAMBAHAN POZZOLAN ALAM BATU APUNG TERHADAP KARAKTERISTIK GENTENG (STUDI KASUS GENTENG PLENTONG EX. PEJATEN) - Ari Sanjaya, I Putu (Jurnal Ilmiah Teknik Sipil; Vol. 12, No. 2 Juli 2008)
Research about influence of addition of natural pozzolan pumice in making of Pejaten ceramic tile was conducted. This research was conducted based on condition that in the recent time the tile industries in Bali have experienced degradation of quality compared to existing marketing tile. The natural pozzolan pumice was selected as an additive because this pumice is less exploited and highly contained SiO2 component. If burned this component will yield silica/glass materials and filled the tile void. This research was conducted to obtain the influence of addition of natural pozzolan pumice to ceramic tile characteristics such as bending strength, water absorption, and water infiltration. The ceramic tiles were made by mixing of clay, paras powder, natural pozzolan pumice and water. The mixture consisted of paras powder counted by 20% from clay weight, natural pozzolan of pumice counted by percentage addition of paras powder. Addition of natural pozzolan pumice was 5%, 10%, 15% from paras powder weight. The process started from preparation of materials, mixing of materials, hulling, molding, draining and burning at the stove for about 12 hours with temperature of 800oC to 1000oC. Results of the research showed that the addition of 15% natural pozzolan pumice resulted in smallest water absorption, longest time of water infiltration. The value of bending load of the tile was 71,30 kg and bending strength was 0,675 kg/mm2. For plain part of the tile, the average bending load was 14,40 kg and bending strength was 0,250 kg/mm2. The water absorption rate was equal to 26,39% and time of water infiltration was 99 minutes. Shrinkage happened in tile with addition of 15% of natural pozzolan pumice with contraction value of 7,27% in long and contraction value of 9,20% in wide. Standard tile had smaller value of bending load and bending strength than the tile with 15% of natural pozzolan pumice addition, with were 54,90 kg and 0,520 kg/mm2, respectively. For the plain part of standard tile, the value of bending load and bending strength were 11,80 kg and 0,205 kg/mm2, respectively. Largest water absorption value of tile occurred in ceramic tile with addition of natural pozzolan pumice of 5%, which had value of 27,60%. These tiles had fastest water infiltration time with a value of 68 minutes.
Keywords: pejaten tile, paras powder, natural pozzolan pumice, tile characteristics, absorption and infiltration of water